PHRASEOLOGIES AS A MEANS OF SPEECH DEVELOPMENT OF THIRD GRADE STUDENTS IN UKRAINIAN LANGUAGE LESSONS OF THE MOUNTAIN SCHOOL OF THE UKRAINIAN CARPATHIANS - Tkachuk, Oresta (Mountain School of Ukrainian Carpaty, 2020)
The article considers the problem of working with stable language expressions, with which children get acquainted at the initial stage of language learning. Phraseologisms are represented in all spheres of human life, their children hear from parents and acquaintances every day, and therefore they become clear and come into daily use. In mountainous regions, where upbringing takes place in close connection with nature, with a somewhat limited range of communication and the specifics of living conditions, the child perfectly learns from an early age the linguistic richness of his own speech or speech, including stable expressions. However, when children get acquainted with textbooks, younger students often have problems understanding and understanding the content of some phrases that are not used or rarely used in this area. The primary school curriculum provides only a cursory introduction to stable expressions, which encourages some teachers to work unsystematically on phraseology. The article presents the results of a survey of teachers in the Carpathian region with different levels of work experience. The analysis of the survey allowed us to conclude that the work with phraseology in primary school is fragmentary. An attempt to analyze the didactic content of existing textbooks on the Ukrainian language for the third grade led to the conclusion that most exercises are reproductive in nature, although there are those that contain creative elements of tasks. According to the author of the article, the textbook for the third grade of the new Ukrainian school deserves approval (compiled by G. Sapun). The article gives examples of methods of working with Hutsul phraseology in Ukrainian language lessons in the third grade. The given didactic material can be used both in the process of studying phraseology in the system of preparation of students of higher educational institutions, and for development of cognitive activity of pupils of elementary school at lessons of the Ukrainian language, literary reading